RNF121 Inhibits Angiogenic Growth Factor Signaling by Restricting Cell Surface Expression of VEGFR‐2. (21st December 2015) - Maghsoudlou, Armin; Meyer, Rosana D.; Rezazadeh, Kobra; Arafa, Emad; Pudney, Jeffrey; Hartsough, Edward; Rahimi, Nader
Abstract : RING finger protein 121 (RNF121) is an endoplasmic reticulum (ER) ubiquitin E3 ligase that binds to and ubiquitinates the newly synthesized immature vascular endothelial growth factor receptor‐2 (VEGFR‐2). RNF‐121 ubiquitination of VEGFR‐2 inhibits the trafficking of immature VEGFR‐2 from the ER complex to the Golgi apparatus. This restricts the expression of VEGFR‐2 at the cell surface and minimizes the VEGF angiogenic signaling in endothelial cells. Abstract : Ligand stimulation promotes downregulation of RTKs, a mechanism by which RTKs, through the ubiquitination pathway are removed from the cell surface, causing a temporary termination of RTK signaling. The molecular mechanisms governing RTK trafficking and maturation in the endoplasmic reticulum (ER)/Golgi compartments are poorly understood. Vascular endothelial growth factor receptor‐2 (VEGFR‐2) is a prototypic RTK that plays a critical role in physiologic and pathologic angiogenesis. Here we demonstrate that Ring Finger Protein 121 (RNF121), an ER ubiquitin E3 ligase, is expressed in endothelial cells and regulates maturation of VEGFR‐2. RNF121 recognizes newly synthesized VEGFR‐2 in the ER and controls its trafficking and maturation. Over‐expression of RNF121 promoted ubiquitination of VEGFR‐2, inhibited its maturation and resulted a significantly reduced VEGFR‐2 presence at the cell surface. Conversely, the shRNA‐mediated knockdown of RNF121 in primary endothelial cells reduced VEGFR‐2 ubiquitination and increased its cell surface level. The RING Finger domain of RNF121 is required for its activity toward VEGFR‐2, as its deletion significantly reduced the effect of RNF121 on VEGFR‐2. Additionally, RNF121 inhibited VEGF‐induced endothelial cell proliferation and angiogenesis. Taken together, these data identify RNF121 as a key determinant of angiogenic signaling that restricts VEGFR‐2 cell surface presence and its angiogenic signaling.